IMAN DAN AKHLAK DALAM SAINS PERSPEKTIF AL-QUR’AN - Yani, Ahmad (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2022)
Along with the passage of times and era, the development of science and technology is accelerating. In this era of society 5.0, various sophisticated technological innovations were developed, among which were quite viral, such as metaverse technology. The progress of science and technology must be framed with morals, and in the Islamic perspective it must be based on morals, so that science and technology bring great benefit to humans and nature. Because without being framed by morality, the progress of science and technology can become tools and means that destroy the natural order and humanity. This paper uses a literature study method based on the study of the Qur'an. The result of writing is that faith and morals are very important in science. Science without the value of faith and morals will have a detrimental impact in the form of damage in many aspects of life. Morals in the world of science include good morals towards fellow humans, towards animals, towards plants, and towards inanimate objects.